SPATIAL SUSCEPTIBILITY OF ARCHAEOLOGICAL SITES TO EARTHQUAKE ENVIRONMENTAL EFFECTS (EEES) - Minos-Minopoulos, D.; Dominey-Howes, D.; Pavlopoulos, K. (Bulletin of the Geological Society of Greece, 2016)
The study examines a semi-quantitative indicator based method to assess the spatial susceptibility of archaeological sites to the secondary Earthquake Environmental Effects (EEEs) of ground liquefaction, landslides and tsunami. The method was applied at 16 archaeological sites allowing the identification of the EEEs each site is susceptible to and their prioritization at a national and regional level through the Spatial Susceptibility index (SSi). Results indicate that the majority of the sites are susceptible to at least one Earthquake Environmental Effect. This highlights their contribution to the vulnerability of archaeological sitesto earthquake hazard and the necessity for the integration of spatial susceptibility parameters in vulnerability assessment studies for cultural heritage protection.